Discrete Element Simulation Analysis of the Bending and Toppling Failure Mechanisms of High Rock Slopes. (31st January 2021) - Meng, Zhigang; Hou, Yongli; Guo, Longji; Wang, Fengnian; Liu, Kuiming; Qi, Gan; Ma, Juan
Abstract : The high rock slope situated in the Southwest stope of Taiping Mining, Inner Mongolia, is subject to dumping failure due to its instability. The dumping body rock layer of this stope shows obvious bending and lowering of the head. The overturning angle of the rock strata can reach 46°, and tension dislocation along the rock joint can be observed in exposed sections and at the bedding and lithologic interface. The sliding surface also displays a broken line morphology. Through evaluation of regional rock integrity parameters and rock soft and hard parameters, rock-mass strength based on Hoek Brown strength estimation criteria can be developed. Based on the discrete element method, the geological model of layered excavation of the thin layer slope can be constructed. Combined with indoor and outdoor assessments, the characteristics of toppling deformation of the thin layer open-air slope can be studied and summarized. In this study, simulation analysis showed that under first excavation conditions, a crack-, dump-, and antislip zone was formed. The rock in the crack zone formed a "<"-shaped fracture along the slope surface that was squeezed towards the bottom of the slope. In the lower dumping area, the deflection angle gradually increased with excavation, and the deformation range and levels in the antislip area increased with excavation. Following the third excavation, the antisliding zone disappeared and the toppling line changed from a broken line to a straight line. In the final state, the slope collapsed as a whole, with the collapse of the dumping body penetrating the top to the foot of the slope.